Nitrogen and carbon assimilation by Saccharomyces cerevisiae during Sauvignon blanc juice fermentation. Issue 8 (17th November 2014) - Pinu, Farhana R.; Edwards, Patrick J.B.; Gardner, Richard C.; Villas‐Boas, Silas G.
Abstract To investigate the assimilation and production of juice metabolites by Saccharomyces cerevisiae during winemaking, we compared the metabolite profiles of 63 Sauvignon blanc (SB) grape juices collected over five harvesting seasons from different locations of New Zealand before and after fermentation by the commercial wine yeast strain EC1118 at 15 °C. Metabolite profiles were obtained using gas chromatography–mass spectrometry and nuclear magnetic resonance and the oenological parameters were determined by Fourier transform infrared spectroscopy. Our results revealed that the amino acids threonine and serine were the most consumed organic nitrogen sources, while proline and gamma‐aminobutyric acid were the least consumed amino acids during SB juice fermentation. Saccharomyces cerevisiae metabolised some uncommon nitrogen sources (e.g. norleucine, norvaline and pyroglutamic acid) and several organic acids, including some fatty acids, most likely after fermenting the main juice sugars (glucose, fructose and mannose). However, consumption showed large variation between juices and in some cases between seasons. Our study clearly shows that preferred nitrogen and carbon sources were consumed by S. cerevisiae EC1118 independent of the juice fine composition, whilst the consumption of other nutrient sources mainly depended on the concentration of other juice metabolites, which explains the uniqueness of each barrel of wine.